2020
DOI: 10.1016/j.psychres.2020.113254
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic symptoms in COVID-19 patients. A retrospective descriptive study

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
137
1
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(166 citation statements)
references
References 32 publications
6
137
1
16
Order By: Relevance
“…The copyright holder for this preprint this version posted August 16, 2020. ; https://doi.org/10.1101/2020.08.14.20175190 doi: medRxiv preprint 15/22 an insomnia diagnosis were also markedly elevated (HR 1⋅9-3⋅3), again in keeping with predictions that circadian disturbances will follow COVID-19 infection. In contrast, we did not find a clear signal for psychotic disorders despite case reports suggesting that this might occur 13,27 . Lastly, the 2-3 fold increased risk of dementia after COVID-19 extends findings from previous case series 13, 28 and is particularly concerning.…”
Section: Discussioncontrasting
confidence: 99%
“…The copyright holder for this preprint this version posted August 16, 2020. ; https://doi.org/10.1101/2020.08.14.20175190 doi: medRxiv preprint 15/22 an insomnia diagnosis were also markedly elevated (HR 1⋅9-3⋅3), again in keeping with predictions that circadian disturbances will follow COVID-19 infection. In contrast, we did not find a clear signal for psychotic disorders despite case reports suggesting that this might occur 13,27 . Lastly, the 2-3 fold increased risk of dementia after COVID-19 extends findings from previous case series 13, 28 and is particularly concerning.…”
Section: Discussioncontrasting
confidence: 99%
“…A surveillance study in the United Kingdom (UK) showed that 39 cases of a cohort of 125 COVID-19 hospitalized patients with neurological manifestations presented with altered mental status, with encephalopathy in 16 and neuropsychiatric syndromes in 23 of them, mostly new-onset psychosis (n = 10) or other related psychiatric disorders (n = 7) (Varatharaj et al, 2020). In line with this evidence, in a retrospective descriptive study from a hospital in Madrid, Spain, 10 patients with a lab-confirmed diagnosis of COVID-19 and new-onset psychotic symptoms were identified among 10,000 patients with symptoms compatible with COVID-19 assessed between March and April 2020 in the emergency department (Parra et al, 2020). They had a mean age of 54.1 years, and psychiatric symptoms, mainly delusion, orientation/attention disturbances and auditory hallucination (in 10, 6, and 4 cases, respectively), appeared primarily after the first typical COVID-19 symptoms and were resolved in less than 2 weeks (Parra et al, 2020).…”
Section: Neuropsychiatric Manifestations Of Covid-19mentioning
confidence: 59%
“…In line with this evidence, in a retrospective descriptive study from a hospital in Madrid, Spain, 10 patients with a lab-confirmed diagnosis of COVID-19 and new-onset psychotic symptoms were identified among 10,000 patients with symptoms compatible with COVID-19 assessed between March and April 2020 in the emergency department (Parra et al, 2020). They had a mean age of 54.1 years, and psychiatric symptoms, mainly delusion, orientation/attention disturbances and auditory hallucination (in 10, 6, and 4 cases, respectively), appeared primarily after the first typical COVID-19 symptoms and were resolved in less than 2 weeks (Parra et al, 2020). These episodes were considered atypical since patients had no familiar history of psychiatric disorders, no substance use disorders, had an atypical age of onset, and presented a fast recovery (Parra et al, 2020).…”
Section: Neuropsychiatric Manifestations Of Covid-19mentioning
confidence: 73%
See 2 more Smart Citations